A D-Shaped Fiber Long-Range Surface Plasmon Resonance Sensor With High Q-Factor and Temperature Self-Compensation - Wang, Qi; Jing, Jian-Ying; Wang, Xue-Zhou; Niu, Li-Ye; Zhao, Wan-Ming (IEEE transactions on instrumentation and measurement, 2020)
A D-shaped fiber based long-range surface plasmon resonance (LRSPR) sensor with high quality factor ( Q -factor) of 67.75 RIU −1 and temperature self-compensation was proposed and demonstrated. The multilayered architecture of the LRSPR sensor consisted of fiber/dielectric buffer layer (DBL)/Au film/analyte, and the deep penetration depth and long propagation distance of long-range surface plasmon polaritons made the LRSPR sensor possess high Q -factor. The temperature-sensitive photoabsorption characteristic of the Terbium(III) complexes was utilized to provide temperature self-compensation for the refractive index (RI) measurement of the LRSPR sensor, and the LRSPR sensor realized simultaneous measurement of RI and temperature at the exact same location, which could eliminate the measurement error introduced by temperature to RI measurement. The simulation analysis, supported by finite element analysis (FEA) based on coupled-mode theory, was presented in detail. The simulation results showed that the electric field intensity on the surface of the LRSPR sensor was 2.52 times higher than that of the surface plasmon resonance (SPR) sensor and the sensitivity of the LRSPR sensor increased by 947.31 nm/RIU compared with the SPR sensor, implying the LRSPR sensor possessed more excellent sensing performance. An SPR sensor and a Terbium(III) complex-based LRSPR sensor were developed, and their RI sensing performance was systematically studied and tabulated. The experimental results showed that the Q -factor of the LRSPR sensor was 2.56 times higher than that of the SPR sensor, which agreed well with the simulation results. The LRSPR sensor proposed in this paper possessed higher detection precision and presented greatly promising application prospects in the field of biochemistry.